Psychological status among Emergency Department personnel in Hospital Universiti Sains Malaysia - Kadir, Fairrul (2016)
OBJECTIVE: The aim of this study is to determine the psychological status, particularly level of depression, anxiety and stress level among Emergency Department personnel in Hospital Universiti Sains Malaysia and its association to demographic factors. METHODS: This prospective cross-sectional study was conducted in Emergency Department (ED) Hospital Universiti Sains Malaysia from March to June 2014. A total of 122 personnel from the ED who fulfilled the inclusion criteria were included in the study. Each personnel was given a set of questionnaire consisting demographic background and the DASS 21 form. Demographic factors assessed were age, gender, race, profession and years of working experience. RESULTS: The results from 122 personnel showed a total of 2 personnel (2%) recorded score for moderate depression, 5 personnel (4%) recorded for moderate anxiety and 3 personnel (2%) recorded for severe anxiety. No personnel recorded for moderate-severe stress. Among the demographic factors tested, statistically significant associations were found between stress levels with age, profession and working experience of personnel. Significant associations were also found between depression levels with the gender of personnel. CONCLUSION: The psychological status, particularly depression, anxiety and stress level among ED personnel were generally low. The stress level was noted to be most affected by demographic factors compared to depression and anxiety.